Muscarinic control of the hyperpolarization-activated current (if) in rabbit sino-atrial node myocytes. - DiFrancesco, D (1988)
1. The mechanism by which acetylcholine (ACh), by stimulation of muscarinic receptors, acts to inhibit activation of the hyperpolarization-activated 'pacemaker' current, if was investigated in isolated rabbit sino-atrial (SA) node myocytes. 2. Intracellular loading with GTP gamma S, a non-hydrolysable analogue of GTP, did not impair the ACh action on if, but made it irreversible. On the other hand, the ACh action on if disappeared after a few minutes of cell loading with GDP beta S, a GDP analogue known to bind to G-proteins and prevent their receptor-stimulated action. Furthermore, incubation of cells in a solution containing pertussis toxin (PTX) led to abolition of the if response to ACh. These results indicate that the inhibitory effect of ACh on if is mediated by G-proteins activated by muscarinic receptors. 3. Intracellular loading with phosphodiesterase (PDE) increased the rate of if current run-down, but did not abolish the inhibitory action of ACh on if. 4. Extracellular perfusion with isobutylmethylxanthine (IBMX), a PDE inhibitor, increased if activation by shifting the current activation range to more positive voltages, as inferred by a three-pulse protocol analysis; in the presence of IBMX, the inhibition of if by ACh was not abolished. 5. The ACh-induced if depression persisted also in cells loaded with cyclic GMP. In these cells, as in those loaded with PDE, the if run-down was fast. 6. Oxotremorine, a muscarinic agonist coupled to adenylate cyclase but not to phosphoinositide turnover in cardiac cells, simulated ACh in its inhibitory action on if. The above results rule against the ACh action being mediated by PDE or by phosphoinositide turnover. 7. To investigate the possible involvement of cyclic AMP as a second messenger in the ACh action on if, we loaded cells with cyclic AMP and IBMX; under these conditions the action of ACh disappeared within a few minutes of whole-cell recording. 8. In cells where the slow inward Ca2+ current (isi) was measured together with if, ACh was seen to depress both currents. 9. In cells superfused with forskolin, the if amplitude on stepping to the half-activation voltage range was enhanced as a consequence of a depolarizing shift of the activation curve; ACh was not effective on if following stimulation by forskolin, but strongly depressed in the same cell the if current stimulated to a similar degree by isoprenaline.(ABSTRACT TRUNCATED AT 400 WORDS)